Determinant Faktor Yang Mempengaruhi Islamic Social Reporting Pada Perusahaan Pertanian Yang Terdaftar Di Indeks Saham Syariah Indonesia (ISSI) Tahun 2012-2015 - Hidayah, Khusnul; Wulandari, Wahyu Mas (Universitas Islam Negeri Raden Intan Lampung, 2017)
The development of Corporate Social Resposibility is not only applied at the conventional company, but also thrive in Islamic-based business economy that is often referred as the Islamic Social Reporting (ISR). The company that reported their liabilities in the form of ISR assumes that an entity is not only being required to do accountability to internal and external parties but more is the existence of an obligation to do accountability to Allah SWT.As an agricultural company wjich has been listed on the Indeks Saham Syariah Indonesia (ISSI) was supposed to do the disclosure of ISR in accordance with Sharia principles. This is necessary to meet the importance of muslim stakeholders who want social activityinformationwhich is undertaken by a syari’ah company.This research was aimed to analyze the factors that affect the disclosure of ISR. The population in this research was the entire agricultural companies listed on the Indeks Saham Syariah Indonesia (ISSI) in the Bursa Efek Indonesia.The selection of the sample used the purposive samplingmethod with criteria of agricultural sector companies who conducted disclosure of ISR and consistently at ISSI in the year of 2012– 2015. The samples is 11 companies. Data analysis technique that was used in this research is a multiple regression analysis method.The results of this research indicated that there was a significant influence among all independent variables simultaneously against the dependent variable. Partially it indicated that profitability, proportion of independent commissioner, the size of the company, and the age of the company which has an influence on disclosure of Islamic Social Reporting.